Patchy nuclear chain reactions - Eric Dumonteil; Rian Bahran; Theresa Cutler; Benjamin Dechenaux; Travis Grove; Jesson Hutchinson; George McKenzie; Alexander McSpaden; Wilfried Monange; Mark Nelson; Nicholas Thompson; Andrea Zoia (Communications Physics, 2021)
Understanding and predicting fluctuations of the neutron population within a nuclear reactor is of fundamental importance for nuclear safety, especially in connection with reactor control at startup and shutdown. The study presents experiments and Monte Carlo simulations of persistent neutron fluctuations and correlations (stochastic noise and neutron clustering) in nuclear reactors which are interpreted by stochastic modelling based on branching random walks.